BK virus-associated hemorrhagic cystitis after pediatric stem cell transplantation - Seung Beom Han; Bin Cho; Jin Han Kang (Korean Pediatric Society, 2014)
Hemorrhagic cystitis is a common stem cell transplantation-related complication. The incidence of early-onset hemorrhagic cystitis, which is related to the pretransplant conditioning regimen, has decreased with the concomitant use of mesna and hyperhydration. However, late-onset hemorrhagic cystitis, which is usually caused by the BK virus, continues to develop. Although the BK virus is the most common pathogenic microorganism of poststem cell transplantation late-onset hemorrhagic cystitis, pediatricians outside the hemato-oncology and nephrology specialties tend to be unfamiliar with hemorrhagic cystitis and the BK virus. Moreover, no standard guidelines for the early diagnosis and treatment of BK virus-associated hemorrhagic cystitis after stem cell transplantation have been established. Here, we briefly introduce poststem cell transplantation BK virus-associated hemorrhagic cystitis.